Worker competence and safety performance the mediation role of safety orientation in construction industry - Mehdi Pourmazaherian; Innocent Musonda (Taylor & Francis Group, 2022)
Health and safety issues have always been a major problem and concern in the construction industry. Although substantial improvements in construction safety have achieved in the past decades, the industry lags other industries on safety. Therefore, this research is to explore the worker's behaviour about safety performance, mainly focusing on worker's competence mediated by safety orientation on safety performance. A questionnaire survey was used for this study validated by the experts. In all, 600 respondents were randomly selected from government and private construction industries and yielded a response rate of 430 (71.6%). Additionally, correlational analysis and structural equation modeling (SEM) were used to examine the research hypotheses. The finding showed that worker's competence has a significant impact on safety performance. Indeed, safety orientation mediated the relationship between worker competence and safety performance. Thus, this study carries values to the Sustainable Development Goals (SDG) such as goal 3 (SDG 3) that tries to enhance the good health & well-being of the societies and workplace through the investigation of the effective factors on the safety performance of the construction industry. Ultimately, the findings of this study contribute to the achievement of Sustainable Development Goal 8 (SDG 8) through encouraging the entrepreneurship as are effective measures to eradicate or decrease forced labour, slavery, and incompetent worker at the workplace (focusing on behavioural aspects). In this regard, the goal is to achieve full and productive employment and decent work, for all women and men by 2030.